Government Political Communication Confirguration in Governance of Banda Aceh Madani - Zahari Zahari (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the configuration of government political communication in managing the Banda Aceh Madani city government and to analyze the mayor's political communication commitment in building a civil society Banda Aceh city. This research was designed as a descriptive qualitative research. The key informants in this study were the mayor of Banda Aceh, the Banda Aceh city government work unit and the Banda Aceh community. Data collection techniques are in-depth interviews, observation, and documentation study. The theory used in this research is organizational structure theory and Islamic communication. Research findings, the political communication configuration of the Banda Aceh city government in managing the government is carried out with various political actors ranging from Acehnese Ulama leaders, Banda Aceh regional stakeholders, Banda Aceh city government work units and the Banda Aceh city community both at each sub-district and lower-level village. The Banda Aceh city government gets political support to carry out executive and legislative functions in making Banda Aceh a civil city. The supporting factors for the political communication of the Banda Aceh city government are legal legality, economy, community culture, and security. The political communication commitment of the Banda Aceh city government in managing the government and building the Banda Aceh city community as a civil city community has begun to form. The political commitment of the Banda Aceh city government includes building Islamic law as a whole, building good governance, building a populist economy, fostering an intellectual, healthy and prosperous society, who master a variety of science, technology, arts and culture, build Islamic tourism infrastructure, increasing women's participation in the public sphere, and child protection, building the role of the younger generation as a development force. Recommendations and advice necessary communication configuration and the commitment of political communication Banda Aceh city government sustained and sustainable dignity for all the people of Banda Aceh in Banda Aceh city government organize civil.